Development of a Flipbook of Cergam Siwak about the Appreciation of Al-Wahhab and Al-Kabir in Grade 3 in Islamic Education - Hayati, Anisa Nur; Sidik, Alya Setiani; Cofia, NG. Shofi Isis; Aeni, Ani Nur (Lembaga Yasin AlSys, 2025)
Education plays an essential role in the civilization of a nation. However, many students still have difficulty understanding the knowledge delivered by teachers, including in Islamic Education (PAI) subjects, especially the appreciation of Asmaul Husna Al-Wahhab and Al-Kabir. This research aims to develop a learning media product as a digital flipbook, namely CERGAM SIWAK (Illustration Story of Al-Wahhab and Al-Kabir). The method used is Design and Development (D&D) with the ADDIE model approach (Analyse, Design, Development, Implement, and Evaluate). This research was conducted on 25 grade 3 students at MI Al-Ishlah Sulambitan, Ganeas, Sumedang, West Java. The research results showed that this flipbook received a media validation percentage of 95% and a material validation of 77.5%. It indicates that this product is very good and worthy of being used as a tool in PAI learning. Thus, CERGAM SIWAK is expected to improve students' appreciation of Al-Wahhab and Al-Kabir in educational institutions, especially religious education.